Yield performance of oyster mushroom (Pleurotus ostreatus) on different substrates - Das, D; Kadiruzzaman, M; Adhikary, SK; Kabir, MY; Akhtaruzzaman, M (Bangladesh Journal of Agricultural Research, 2014)
An experiment was conducted at Mushroom Lab of Horticulture Centre under Department of Agricultural Extension (DAE), Khairtala, Jessore to determine the performance of different substrates on the yield of oyster mushroom (Pleurotus ostreatus). Sugarcane bagasse, sawdust, and coconut coir individually and their combinations were used as substrates. The experiment was laid out in Completely Randomized Design (CRD) with five replications. Data were taken from 1st and 2nd flush of different growth and yield attributes of mushroom. The maximum number of effective fruiting bodies was obtained from sawdust (40) and the lowest number (31.6) from combination of sawdust and coconut coir (1:1). In the 1st flush, the maximum weight of individual fruiting body was observed in coconut coir and minimum in sawdust. The highest biological (186.06 g) and economic yield (180.64 g) were obtained from coconut coir and the lowest from sugarcane bagasse. The maximum and minimum harvest index was found in 1st flush at coconut coir and combination of sawdust and sugarcane bagasse (1:1), respectively. Most yield attributes were found higher in coconut coir. Economic yield was positively correlated to number of effective fruiting bodies, pileus diameter, and biological yield. DOI: http://dx.doi.org/10.3329/bjar.v38i4.18946 Bangladesh J. Agril. Res. 38(4): 613-623, December 2013